Improving Teacher Communication Skills Through Personality Variables and Perceptions of The Social Environment - Hendro Prasetyono; Dika Ayuning; Ira Pratiwi Ramdayana; Sri Hapsari (FKIP Universitas Lampung, 2023)
Improving Teacher Communication Skills through Personality Variables and Perceptions of the Social Environment. This study aims to comprehensively understand the influence of perceptions of personality and social environment on the communication skills of high school teachers. The research approach is quantitative with a survey method. The total sample is 209 teachers as a sample of 439 teacher population in Central Java Province, Indonesia by simple random sampling method. Data analysis used prerequisite analysis test and inferential statistics with path analysis. Analysis and interpretation of the data shows that an increase in the dominant type of flexibility of the teacher's personality improves the teacher's communication skills. The increased similarity of perceptions of the teacher's social environment results in an increase in the teacher's communication skills. Increasing the dominant type of teacher personality flexibility results in an increase in the similarity of perceptions of the teacher's social environment. Conclusion: improving teacher communication skills can be through personality flexibility and perception of the social environment. Keywords: communication skills, personality, social environment, path analysis, high school.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202353